Nutrient mobilization and crop assimilation as influenced by nutrient management strategies under direct seeded basmati rice (Oryza sativa) – based cropping systems - VERMA, RAKESH KUMAR; SHIVAY, YASHBIR SINGH; CHOUDHARY, MUKESH; GHASAL, PRAKASH CHAND; MADAR, RAGHAVENDRA (The Indian Journal of Agricultural Sciences, 2020)
The field experiment was carried out for two consecutive years (2014–2016) in split-plot design to investigate the effect of integrated nutrient management and crop diversification through inclusion of legume and vegetable crops in direct seeded basmati rice (Oryza sativa L.)–based cropping systems (DSRB) on nutrient availability for crop uptake. The study involved four cropping systems (CS) in main plots (DSBR‒wheat‒fallow (CS1), DSBR‒wheat‒greengram (CS2), DSBR‒cabbage‒greengram (CS3) and DSBR‒cabbage‒onion (CS4) and four nutrient management strategies under subplots (unfertilized (NS0), 100% recommended dose of fertilizers (RDF) (NS1), 50% RDF + 25% recommended dose of nitrogen (RDN) through leaf compost (LC) + biofertilizer (NS2), 50% RDF + 25% RDN through vermicompost (VC) + biofertilizer (NS3)). The results revealed that diversification of rice–wheat system with legume (greengram) or vegetable (cabbage and onion) crops and integrated nutrient management strategies had positive effect on nutrient uptake and available nutrient status in the soil. Significantly higher uptake of N, P and K in all crops and Zn, Fe, Mn and Cu in rice and wheat were observed with NS2 and NS3 as compared to NS0. Available N, P and K status were significantly higher in NS2 and NS3 as against NS0 and NS1. Inclusion of cereal crops in the cropping systems showed a negative apparent N balance, but inclusion of vegetable crops in the cropping systems exhibited positive apparent N balance under different nutrient management strategies except NS0. The highest positive apparent N balance was observed in NS1 treatment. The apparent P balance was found to be positive in all the cropping systems with all the nutrients sources except NS0. Apparent K balance was found negative in all the cropping systems under different nutrient management strategies. Thus, cropping systems with summer greengram, cabbage and onion (CS2, CS3 and CS4) under integrated nutrient management practices (NS2 and NS3) were found more sustainable after two years of cropping cycle and can be advocated by the farmers of IGP.